The Effects of An Empowerment Program on The Psychosocial Rehabilitation Abilities of Caregivers of Schizophrenic Patients - ดีหลี, สิริมาบังอร; สมประเสริฐ, ชมชื่น; บรรทุมพร, นุชนาถ (Journal of The Royal Thai Army Nurses, 2019)
The present study was based on a quasi-experimental research design aimed at studying the effects of an empowerment program on the psychosocial rehabilitation abilities of caregivers of schizophrenic patients. The sample included 60primary caregivers of schizophrenic patients living in Huai Thap Than District, Sisaket Province,Thailand that met the inclusion criteria and that were randomized into experimentaland control groups, with 30 persons per group. The control group received routine caring activities. The research instruments were the following: 1) personal data; 2) an empowerment program; and 3) a psychosocial rehabilitation ability scale. The empowerment program was validated for content validity by 3 experts and the reliability of the psychosocial scalehad a Cronbach’s alpha coefficient of .98. Personal data were analyzed using descriptive statistics and hypothesis tested using dependent and independent t-test. The findings were as follows: 1) The psychosocial rehabilitation ability mean score of the caregivers after participating in the empowerment program (M = 102.50, SD = 6.06) was higher than before joining the program (M = 53.60, SD = 11.60), with a significant difference (t = 20.68, p< .001). 2) The mean difference between the pre-post psychosocial rehabilitation ability mean scores of the schizophrenic patients’ primary caregivers in the experimental group ( = 48.9, SD = 12.95) was significantly greater than that for the primary caregivers of the individuals that received regular caring activities ( = 0.64, SD = 3.05) (t = 19.87, p< .001). This study shows that an empowerment program of this type can enhance the psychosocial rehabilitation abilities of caregivers of schizophrenic patients and can be an alternative design for activities or programs to empower the caregivers of schizophrenic patient in terms of their psychosocial rehabilitation abilities.